BIOINDICATION TOXICITY OF TECHNICAL AND INDUSTRIAL WATER FOR DOPOMOHOYUHILLYASTOVUSYH CRUSTACEANS CERIODAPHNIA AFFINIS LILLJEBORG - and; and (Municipal economy of cities. Series: «Economy science», 2013)
Found that technical industrial waste water electroplating plants of JSC "Motor Sich" can be used for reversible use in industrial needs. When diluted 1:5, 1:8 were observed acute lethal toxicity test culture Ceriodaphnia affinis Lilljeborg.